2014
DOI: 10.1364/ol.39.001819
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid multiphoton and optoacoustic microscope

Abstract: We present a hybrid microscope combining multiphoton microscopy incorporating second-harmonic generation contrast and optical-resolution optoacoustic (photoacoustic) microscopy. We study the relative performance of the two systems and investigate the complementarity of contrast by demonstrating the label-free imaging capabilities of the hybrid microscope on zebrafish larvae ex vivo, concurrently visualizing the fish musculature and melanocytes. This implementation can prove useful in multiparametric microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
2

Relationship

4
6

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 16 publications
(17 reference statements)
0
46
0
Order By: Relevance
“…One possibility for future systems would be to combine optical and optoacoustic systems so as to benefit from both the high resolution of an optical microscope and the larger imaging depth of an optoacoustic system. It has already been shown that optoacoustic microscopy can be integrated into an confocal or multiphoton microscope and deliver complementary contrast [83][84][85], but the full potential of combining the two techniques has not been reached yet.…”
Section: (A) (B) (C) (D)mentioning
confidence: 99%
“…One possibility for future systems would be to combine optical and optoacoustic systems so as to benefit from both the high resolution of an optical microscope and the larger imaging depth of an optoacoustic system. It has already been shown that optoacoustic microscopy can be integrated into an confocal or multiphoton microscope and deliver complementary contrast [83][84][85], but the full potential of combining the two techniques has not been reached yet.…”
Section: (A) (B) (C) (D)mentioning
confidence: 99%
“…The MP microscope used in this study is similar to one previously described [25]. In brief, MPAF and SHG images were obtained using a properly modified inverted microscope (AxioObserver.D1, Zeiss, Jena, Germany) coupled to an Yb-based solid-state femtosecond laser oscillator, emitting near infrared pulsed light at a central wavelength of 1043 nm (YBIX, Time-Bandwidth, Zurich, Switzerland; pulse width: 170 fs, output average power: 2.8 W, repetition rate: 84.4 MHz).…”
Section: Multi-photon Microscopymentioning
confidence: 99%
“…While fluorescence provides a scattering contrast, optoacoustic technology provides an absorption contrast. 111,112 Several systems have been developed for optoacoustic imaging. Portable, hand-held imaging probes can reach 1.5 cm in depth at a speed of 10 volumetric frames per second and a spatial resolution of 200 µm.…”
Section: Optoacoustic/photoacoustic Imagingmentioning
confidence: 99%